Metafisika Hukum Islam: Antara Takdir Ilahi Dan Kebebasan Manusia - Hafidz Miftahuddin, Abdul; Alimatul, Nihdia (JAS MERAH: Jurnal Hukum dan Ahwal al-Syakhsiyyah, 2025)
This article examines the relationship between metaphysics, divine destiny, and human freedom from the perspective of Islamic law. The metaphysics of Islamic law places Allah SWT as the supreme source of law, so that every provision of sharia has a divine basis that transcends mere social construction. In this context, Islamic law is not only viewed as a normative text, but also as a reflection of the absolute will of God. The discourse on destiny (qadha and qadar) opens up a space that contains both determinism and human freedom. The Jabariyah emphasize the complete domination of God's power, the Qadariyah affirm absolute human freedom, while Ahlus Sunnah wal Jama'ah presents a middle ground through the concept of kasb. From this dialectic, it is clear that human freedom in Islam is always accompanied by moral responsibility, both as a servant of God and as a caliph on earth. Thus, Islamic law is built on a harmony between divine determinism and human endeavor, thus giving rise to a legal system that is just, ethical, and oriented towards the welfare of the people.